2005
DOI: 10.1007/s10803-004-1026-6
|View full text |Cite
|
Sign up to set email alerts
|

Access and Service Use by Children with Autism Spectrum Disorders in Medicaid Managed Care

Abstract: Although Medicaid is the largest public payer of behavioral health services, information on access and utilization of services is lacking, and no data on the frequency of service use or types of services provided for children with autism spectrum disorders (ASDs) are available. As states move toward managed care approaches for their Medicaid program, services information is critical. Behavioral health service data for children with autism spectrum disorders were collected from a state Medicaid Managed Care (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 18 publications
(15 reference statements)
2
60
1
Order By: Relevance
“…Single parents may also find it impossible to participate in such trials. Findings from ASD studies report that URM families with a child with ASD experience more difficulties accessing services than Whites (17)(18)(19). However, the findings from our study reported otherwise.…”
Section: Discussioncontrasting
confidence: 88%
“…Single parents may also find it impossible to participate in such trials. Findings from ASD studies report that URM families with a child with ASD experience more difficulties accessing services than Whites (17)(18)(19). However, the findings from our study reported otherwise.…”
Section: Discussioncontrasting
confidence: 88%
“…In general, children with ASD are an under-identified and underserved group of children whose behavioral health needs are unmet (Ruble et al 2005). Behavioral therapy accounted for the largest proportion of health expenses (54.3 %) for ASD children in China (Wang et al 2012).…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…This is in part due to the apparent increase in the prevalence of ASD (Blaxill 2004). While there is controversy around whether this trend is due to an increase in awareness, changes in diagnostic practices, or a true increase in ASD (Fombonne 2005), the heightened demand for autism services is clear (Ruble et al 2005). The resulting strain on the service system has led to an interest in issues of unmet need.…”
Section: Implications and Recommendations For Policy And Practicementioning
confidence: 99%